2013
DOI: 10.1038/ncomms3466
|View full text |Cite
|
Sign up to set email alerts
|

Ordered bilayer ruthenium–platinum core-shell nanoparticles as carbon monoxide-tolerant fuel cell catalysts

Abstract: Fabricating subnanometre-thick core-shell nanocatalysts is effective for obtaining high surface area of an active metal with tunable properties. The key to fully realize the potential of this approach is a reliable synthesis method to produce atomically ordered core-shell nanoparticles. Here we report new insights on eliminating lattice defects in core-shell syntheses and opportunities opened for achieving superior catalytic performance. Ordered structural transition from ruthenium hcp to platinum fcc stacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
178
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(188 citation statements)
references
References 52 publications
10
178
0
Order By: Relevance
“…CO electro-oxidation is important for both proton-exchange membrane fuel cells [1][2][3] and direct methanol fuel cells [4,5]. Due to its importance, CO electro-oxidation has been extensively studied for many years.…”
Section: Introductionmentioning
confidence: 99%
“…CO electro-oxidation is important for both proton-exchange membrane fuel cells [1][2][3] and direct methanol fuel cells [4,5]. Due to its importance, CO electro-oxidation has been extensively studied for many years.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, it was found that the catalyst and the proper non-aqueous electrolyte are the key factors to address these problems. 8 Therefore, various electrocatalysts, including carbons, metal oxides, metal nitrides and precious metals have been examined as the cathode catalysts in Li-O 2 cells to lower the charge overpotential. 9 It was reported that the use of catalysts can decrease the charge potential tõ 3.8 from~4.2 V. 10 It has been shown, however, that the theoretical overcharge potential for a Li 2 O 2 film is only 0.2 V, if there are no limitations on charge transport through Li 2 O 2 to the Li 2 O 2 -electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the combination of multiple materials in complex core-shell nanoparticles and the use of advanced synthesis procedures allow for new functionalities as well as increased flexibility in structure design [47][48][49]. Implementing this concept for plasmonic gas sensing, Ghodselahi et al have demonstrated the use of Cu@CuO core-shell nanoparticles for the detection of carbon monoxide [50].…”
Section: Engineered Nanoparticles and Smart Dustmentioning
confidence: 99%